2022
DOI: 10.1021/acsaelm.2c00123
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Candlelight Organic LED on Mica

Abstract: Candlelight-style, blue hazard-free light sources have been long desired in order to minimize the threats of blue emission on human health, artifacts, ecosystems, and night skies. Flexible light sources can enable numerous innovative products that are wearable, rollable, foldable, and portable. If also transparent, more applications including smart displays, lighting, signage, etc., can be implemented. However, current flexible lighting sources have issues like the use of environmentally unfriendly materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…To explore if some of the threats can be quantified, a few studies were carried out about the effect of wavelength on photoretinitis [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The threat was quantified via the use of a permissible exposure-limit [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. For examples, Okuno et al used the permissible exposure-limit to evaluate the blue-light hazard of various light sources [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore if some of the threats can be quantified, a few studies were carried out about the effect of wavelength on photoretinitis [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The threat was quantified via the use of a permissible exposure-limit [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. For examples, Okuno et al used the permissible exposure-limit to evaluate the blue-light hazard of various light sources [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the maximum permissible exposure limit (MPE), Jou et al also applied a new index, melatonin suppression sensitivity (MSS), to quantify the threat of light at night on melatonin secretion [ 35 ]. They also applied MPE and MSS to demonstrate a fabricated candlelight-style OLED to be eye- and physiologically-more friendly than the blue enriched counterparts [ [32] , [33] , [34] , [35] , [36] , [37] ]. Furthermore, Jou et al reported an easy-to-apply formula and a ready-to-use table derived therefrom to enable a quick determination of the maximum permissible exposure limit (MPE) of any given desk lamp by knowing its labelled color temperature and luminous flux [ 38 ].…”
Section: Introductionmentioning
confidence: 99%